An Introduction to the History of Central Africa, Zambia,Malawi, and Zimbabwe - A,J,Wills (Oxford, 1985)
Revised in light of the most recent research, this new edition brings the story of the Central African region completely up-to-date. Particular attention is given to the liberation struggle and the fortunes of the independent regime of Zimbabwe.